The Impact of Advertising on Consumer Brand Preference: A Focus on Soft-Drink Brands in Nepal - Thakur, Binay Kumar; Singh, Balgopal (Journal of Economics and Management, 2024)
In the soft drink sector in Nepal, this research investigates the influence that advertising has on the preferences of consumers regarding brand names. The purpose of this study is to investigate the ways in which various advertising mediums, including television, social media, and print, influence the preferences of consumers for soft-drink companies. Additionally, the research explores the influence that advertising frequency and digital media have in moulding brand memory, especially among younger consumers. A technique that is quantitative was used, and data was gathered by means of a structured questionnaire that was sent to two hundred respondents in Nepal who came from a variety of age groups and socio-economic backgrounds throughout the country. For the purpose of determining the links between advertisement exposure, brand memory, and brand choice, the data was analysed using regression analysis, chi-square testing, and correlation analysis. The findings indicate that a greater advertising frequency is positively connected with enhanced brand memory. This suggests that frequent exposure to commercials plays a significant role in the maintenance of consumer awareness and brand loyalty. The research has important implications for businesses that sell soft drinks, highlighting the need of placing a strategic emphasis on digital and social media platforms in order to attract younger customers who are very knowledgeable about technology. It also advises that future research should investigate cross-national comparisons and the impact that digital advertising has on brand loyalty over the long term.